Activation of Adenosine Monophosphate—Activated Protein Kinase Reduces the Onset of Diet‐Induced Hepatocellular Carcinoma in Mice. Issue 7 (15th May 2020) - Schmoll, Dieter; Ziegler, Nicole; Viollet, Benoit; Foretz, Marc; Even, Patrick C.; Azzout‐Marniche, Dalila; Nygaard Madsen, Andreas; Illemann, Martin; Mandrup, Karen; Feigh, Michael; Czech, Jörg; Glombik, Heiner; et al.
Abstract : The worldwide obesity and type 2 diabetes epidemics have led to an increase in nonalcoholic fatty liver disease (NAFLD). NAFLD covers a spectrum of hepatic pathologies ranging from simple steatosis to nonalcoholic steatohepatitis, characterized by fibrosis and hepatic inflammation. Nonalcoholic steatohepatitis predisposes to the onset of hepatocellular carcinoma (HCC). Here, we characterized the effect of a pharmacological activator of the intracellular energy sensor adenosine monophosphate–activated protein kinase (AMPK) on NAFLD progression in a mouse model. The compound stimulated fat oxidation by activating AMPK in both liver and skeletal muscle, as revealed by indirect calorimetry. This translated into an ameliorated hepatic steatosis and reduced fibrosis progression in mice fed a diet high in fat, cholesterol, and fructose for 20 weeks. Feeding mice this diet for 80 weeks caused the onset of HCC. The administration of the AMPK activator for 12 weeks significantly reduced tumor incidence and size. Conclusion: Pharmacological activation of AMPK reduces NAFLD progression to HCC in preclinical models. Abstract : A pharmacological activator of the cellular energy sensor AMP‐activated protein kinase was tested in mice with diet‐induced, biopsy‐proven NAFLD. The compound reduced fibrosis progression and the onset of hepatocellular carcinoma.